Model Study to Investigate the Toxic Interaction between Spirotetramat and Myclobutanil on Pheasant Embryos in the Early Phase of Development - Szabó, Rita; Major, László; Buda, István; Saidon, Nadhirah Binti; Lehel, József; Budai, Péter (GEORGIKON FOR AGRICULTURE, 2024)
The toxic effects of the Movento insecticide (100 g/l (9.29 m/m%) spirotetramat) applied alone or in combination with Systhane 20 EW fungicide (200 g/l myclobutanil (19.4 m/m%) were studied on pheasant embryos, in the early phase of embryonic development. The test materials were injected in 0.1 ml volume into the eggs' air chamber on the first incubation day. Subsequently, on the third day of incubation, permanent preparations were made using the embryos to study the early developmental stage. Embryos fixed on microscope slides and stained with osmium tetroxide solution were studied by light microscopy. The embryonic mortality and the occurrence of developmental anomalies were analysed statistically by the Fisher test. Based on the experiment’s results, the embryonic mortality of pheasant embryos increased in every treated groups (individual or combined administration of the chemicals) compared to the control. The differences in the individually treated groups could not be statistically proven. The simultaneous application of Movento and Systhane 20 EW significantly increased the mortality of pheasant embryos compared to the control. Both test substances were embryotoxic in pheasants, and an additive toxic interaction was revealed between Movento and Systhane 20 EW.
Keywords: spirotetramat; myclobutanil; interaction; embryonic mortality; pheasant embryo